The Effect of Physical Therapy Treatment in Patients with Subjective Tinnitus: A Systematic Review - Michiels, Sarah; Naessens, Sebastiaan; Van de Heyning, Paul; Braem, Marc; Visscher, Corine M.; Gilles, Annick; De Hertogh, Willem (Frontiers in Neuroscience, 2016)
Background: Tinnitus is a very common symptom that often causes distress and decreases the patient’s quality of life. Apart from the well-known causes, tinnitus can in some cases be elicited by dysfunctions of the cervical spine or the temporomandibular joint(TMJ). To date however, it is unclear whether alleviation of these dysfunctions, by physical therapy treatment, also decreases the tinnitus complaints. Such physical therapy could be an interesting treatment option for patients that are now often left without treatment. Objectives: The aim of this review was to investigate the current evidence regarding physical therapy treatment in patients with tinnitus. Data sources: The online databases Pubmed, Web of Science, Cochrane and Embase were searched up to March 2016. Two independent reviewers conducted the data extraction and methodological quality assessment. Study eligibility criteria: Only randomized controlled trials and quasi-experimental trials were included in the review. Studies had to be written in English, French, Dutch or German. Participants and interventions: The included studies investigated the effect of physical therapy treatment modalities on tinnitus severity in patients suffering from subjective tinnitus. Results: Six studies were included in this review, four investigating cervical spine treatment and two investigating TMJ treatment. These studies show positive effects of cervical spine treatment (manipulations, exercises, triggerpoint treatment) on tinnitus severity. Additionally, decrease in tinnitus severity and intensity was demonstrated after TMJ treatment, following splints, occlusal adjustments as well as jaw exercises. Limitations: The risk of bias in the included studies was high, mainly due to lack of randomization, lack of blinding of subjects, therapists and/or investigators. Additionally, risk of bias is present due to incomplete presentation of the data and selective reporting. A major issue of the reviewed papers is the heterogeneity of the included study populations, treatments and outcome measures, which inhibit data pooling and meta-analysis. Conclusions: Despite the methodological issues in the included studies and the consequent low quality evidence, it is noteworthy that all included studies show positive treatment effects. Before recommendations can be made, these results need to be confirmed in larger, high quality studies, using unambiguous inclusion criteria, state-of-the-art treatment and high quality outcome measures.